ANALISIS KUALITAS BUTIR SOAL AKHIR SEMESTER (SAS) IPAS KELAS V BERDASARKAN PENDEKATAN CLASSICAL TEST THEORY (CTT) - Hajar, Sitti; Siti Zahra Mulianti Natsir; Akmal, Aedil; Rahmadani Syam, Suci (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the quality of Final Semester Assessment items in the Science and Social Studies subject for Grade V at SDN Minasa Upa, Makassar City, in the 2025/2026 academic year using the Classical Test Theory (CTT) approach. This research employed a descriptive quantitative design involving 30 students. The primary data were collected through documentation methods, including test blueprints, test items, answer keys, and students’ answer sheets, and were supported by questionnaires and interviews with teachers. The quality of test items was analyzed based on five aspects: validity, reliability, difficulty level, discriminating power, and distractor effectiveness. The results showed that 64% of the items were valid and 36% were invalid, with high reliability (KR-20 = 0.79). The distribution of difficulty levels consisted of 12% difficult, 52% moderate, and 36% easy items. A total of 56% of the items had very good discriminating power, although some items showed low and negative indices. All items had at least two functioning distractors, although several options were not optimally functioning. The findings indicate that the overall quality of the test items was categorized as adequate, although several items still require revision, particularly those with low validity and negative discrimination indices.